Association between work schedules and motivation for lifestyle change in workers with overweight or obesity: a cross-sectional study in Japan. Issue 4 (30th April 2020) - Tanikawa, Yukihiro; Kimachi, Miho; Ishikawa, Minoru; Hisada, Tomoichiro; Fukuhara, Shunichi; Yamamoto, Yosuke
Abstract : Objective: To investigate the association between work schedules and motivation for behavioural change of lifestyle, based on the transtheoretical model (TTM) in workers with overweight or obesity. Design: A cross-sectional observational study. Setting: A healthcare examination centre in Japan. Participants: Between April 2014 and March 2016, we recruited 9243 participants who underwent healthcare examination and met the inclusion criteria, namely, age 20–65 years, body mass index (BMI) ≥25 kg/m 2 and full-time workers. Exposure: Night and shift (night/shift) workers were compared with daytime workers in terms of motivation for behavioural change. Primary and secondary outcome measures: The primary outcome was action and maintenance stages of change (SOC) for lifestyle in TTM. In a subgroup analysis, we investigated interactions between characteristics, including age, sex, BMI, current smoking, alcohol habits, hours of sleep and working hours. Results: Overall, 1390 participants (15.0%) were night/shift workers; night/shift workers were younger (median age (IQR): 46 (40–54) vs 43 (37–52) years) and the proportion of men was lesser (75.4 vs 60.9%) compared with daytime workers. The numbers of daytime and night/shift workers in the action and maintenance SOC were 2113 (26.9%) and 309 (22.2%), respectively. Compared with daytime workers, night/shift workers were less likely to demonstrate action and maintenance SOC (adjusted OR (AOR): 0.85, 95% CI: 0.74 to 0.98). In a subgroup analysis that included only those with long working hours (≥10 hours/day), results revealed a strong inverse association between night/shift work and action and maintenance SOC (AOR: 0.65, 95% CI: 0.48 to 0.86). A significant interaction was observed between long working hours and night/shift work (P for interaction=0.04). Conclusions: In workers with overweight or obesity, a night/shift work schedule was associated with a lower motivation for behavioural change in lifestyle, and the association was strengthened in those with long working hours.